Micro/macro approach for prediction of matrix cracking evolution in laminated composites. (August 2016) - Ghayour, Mohammadhossein; Hosseini-Toudeshky, H; Jalalvand, Meisam; Barbero, Ever J
A computational constitutive model is presented to predict matrix cracking evolution in laminates under in-plane loading. Transverse cracks are treated as separate discontinuities in the micro-model that provides damage parameters for the macro-model. Both micro- and macro-models are implemented using finite element analysis, specifically, ANSYS, to avoid limitation of analytical micro-modeling. The computational cost of the micro-model is limited to constructing a database of micro-model predictions a priori. The macro-model is simply a finite element analysis discretization of the structure using plane stress or shell elements in ANSYS. The macro-model queries the database, which effectively becomes a constitutive model. The damage surfaces in the database are obtained from the results of large number of finite element micro-scale (unit-cell) analyses. The proposed procedure is implemented in ANSYS as a usermaterial subroutine for transverse crack initiation and propagation in symmetric cross-ply and [0r /(θ / −θ)s /0n ]s laminates under in-plane loads. This method is also examined to study matrix crack evolution in tensile specimen with open hole, and the results found to be in good agreement with available experimental data.